Optimal Scheduling of Combined Heat and Power Generation Considering Heating Grid Dynamics - Merkert, Lennart (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2021)
As the share of renewable generation increases in electric grids, the traditionally heat driven operation of combined heat and power plants (CHPs) reaches its limits. Thermal storage is required for a flexible operation of CHPs. This work proposes three novel methods to use a heating grid as thermal storage by exploiting its thermal dynamics. These include the first approach proving global optimality, a novel linear formulation of grid dynamics and an easily real world applicable approach.